Women, new technology and development : changing nature of gender relations in rural India - SinghaRoy, Debal K.; Centre for Women's Development Studies (New Delhi, India) (New Delhi : Manohar, 1996)
Study conducted by Centre for Women's Development Studies in Madhya Pradesh and Maharashtra.
Keywords: Rural women -- India -- Economic conditions; Women in development -- India; Rural women -- Effect of technological innovations on -- India